The relationship between Roman and local law in the Babatha and Salome Komaise archives : general analysis and three case studies on law of succession, guardianship, and marriage - Oudshoorn, Jacobine G. (Studies on the texts of the desert of Judah ;, 2007)
The discovery of the Babatha archive provided scholars with unique opportunities for reconstructing the life of Jews in second-century Arabia. Although legal issues and especially the question of the relationship between Roman and local law have received attention in a number of publications, this study presents the first complete overview of the legal situation as presented in the Babatha as well as the Salome Komaise archive, using references to law in the documents' texts as the key element for understanding what law is applicable to these documents. By distinguishing between two levels in the papyri, of substantive and of formal law, a new understanding is reached of the part both Roman and local law played in legal reality.